Evaluasi Program Teaching Factory di Sekolah Menengah Kejuruan menggunakan CIPP Framework: Evaluation of the Teaching Factory Program in Vocational High Schools Using the CIPP Framework - Constantinus Rudy Prihantoro; Hari Din Nugraha; Agung Gumelar; David Pratama; Diandra Keisha Gunadi; Fakhrizal Hafish Ibrahim (Jurnal Pendidikan Teknik Mesin Undiksha, 2025)
Teaching Factory is a learning program that optimizes the curriculum, resources, and human capital in Vocational High Schools (SMK) of Centers of Excellence. The objectives of this study are: (1) to identify the level of conformity in the implementation of the Teaching Factory program by analyzing the Context, Input, Process, and Product (CIPP) at five SMKs in DKI Jakarta; and (2) to formulate recommendations for improving and developing the Teaching Factory program to be more effective and sustainable. This research employed a quantitative method with a CIPP-based evaluation instrument, involving vice principals of curriculum and facilities, teachers, and students as research subjects. The findings reveal that: (1) Context: average score 3.61 out of 4, the curriculum is relatively aligned with industry needs, but the understanding of educational regulations remains low due to limited dissemination of government policies to teachers and school management; (2) Input: average score 3.55, facilities and infrastructure are inadequate due to limited budgets and lack of regular equipment calibration, which reduces the quality of marketable products and human resources, although teachers’ pedagogical competence (avg. 3.8) is already good; (3) Process: average score 3.59, learning methods are less innovative as teachers still rely on lectures and employ ineffective assessment instruments, resulting in low collaboration among students and suboptimal graduate employability; (4) Product: average score 3.26, the quality of marketable products falls below industry standards due to weak school quality control systems and the underutilization of project-based assessment. These findings can serve as a basis for strategies and curriculum development that better prepare students for the labor market and help reduce the unemployment rate among SMK graduates.